E-cadherin Interacts With Posttranslationally-Modified AGO2 to Enhance miRISC Activity - Li, Jie-Ning; Sun, Hui-Lung; Wang, Ming-Yang; Chen, Pai-Sheng (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs) are small noncoding RNAs which post-transcriptionally suppress target mRNAs expression and/or translation to modulate pathophyological processes. Expression and function of miRNAs are fine-tuned by a conserved biogenesis machinery involves two RNase-dependent processing steps of miRNA maturation and the final step of miRNA-induced silencing complex (miRISC)-mediated target silencing. A functional miRISC requires Argonaute 2 (AGO2) as an essential catalytic component which plays central roles in miRISC function. We uncovered a post-translational regulatory mechanism of AGO2 by E-cadherin. Mechanistically, E-cadherin activates ERK to phosphorylate AGO2, along with enhanced protein glycosylation. Consequently, the phosphorylated AGO2 was stabilized and ultimately resulted in induced miRISC activity on gene silencing. This study revealed a novel pathway for miRNA regulation through an E-cadherin-mediated miRISC activation.